CONCEPTUAL STUDY OF ORGANIZATION BEHAVIOUR FOR AN EFFECTIVE ORGANIZATION DEVELOPMENT PROCESS - Gaur, Vidhu (International Journal of Psychosocial Rehabilitation, 2019)
The organization is the backbone of the administration because that is an efficientorganization;, the administration does not take into account its functions. In the management process. It is the structural framework of the skills and responsibilities required by the performance of the various functions to achieve the corporate objectives. In other words, the organization is simply a person who works together for a common goal. It is a group of people who, if uncontrolled or if they meet in a place and contribute with the parrot to the creation of a common goal. Managers work through people. They assign resources, direct the activities of others, and make decisions to achieve the organization's goals. The organization is a coordinated social unit, made up of two or more people,thath works to achieve a common goal. Managers are responsible for managing the organization. The world has become a global village. Understanding organizational behavior has become very important for today's managers. Globalization has presented challenges and opportunities for organizational behavior. Various changes are taking place in organizations, such as the increase in the number of women employed, the reduction of thecompany,y and the increase in the number of temporary workers. Business moves where technology is. It can be said that technology has driven the business. There are many challenges and opportunities for managers to use the concepts of organizational behavior. Organizational behavior focuses on improving productivity, reducing absenteeism,turnover,r and deviant behaviors in theworkplace,e and increasing organizational citizenship and job satisfaction. This research paperexploresf what people do in an organization and how their behavior affects the performance of the organization. The following document is conceptual in nature and seeks to explain the behavior of the organization and its role in business management.